The "Saenz Peña Law" and its reception in the electoral legislation in the province of Mendoza (1910-1912) (Res Gesta, 2021)
In april 1912, Mendoza adopted the principles of “Sáenz Peña Law” by enacting new local electoral legislation, becoming the first province to receive its content in its local legislation. But the reformist process began a year earlier, with the proposal of other law, made by Governor Ortega, in the middle of his break with his predecessor -Emilio Civit- and his alignment with the reformist action of the president.This article reconstructs the junctures and the particularities that marked the evolution of the electoral laws in the province, contextualizing such process within the framework of the reconfiguration of the local ruling elite that took place after the “Centenario”. In this framework, we also examine the morphology of the two local electoral laws and the main changes they introduced in the provincial electoral system.  Likewise, the article investigates the assimilation of the new legislation by the local political parties and proposes a reconsideration of the singularity of the Mendoza´s reformist process, in light of what happened in other Argentinian provinces.
Keywords: Ley Sáenz Peña; Reformism; Provincial legislation; Electoral reforms